Common Eider (Somateria mollissima v-nigrum) Nest Cover and Depredation on Central Alaskan Beaufort Sea Barrier Islands - Noel, Lynn E.; Johnson, Stephen R.; O'Doherty, Gillian M.; Butcher, Matthew K. (ARCTIC, 2010)
Female common eiders (Somateria mollissima v-nigrum) generally select nest sites in areas with driftwood cover. Previous studies of common eiders have shown a positive relationship between nest success and driftwood cover. Our observations led us to hypothesize that cover does not enhance nest success when mammalian predators are present. To evaluate nest cover selection in common eiders, we examined five years of nesting data to determine the interactions between the probability of nest activity and the amount of driftwood cover in the presence of avian versus mammalian predators. Most common eider nests were surrounded by low (40%) or moderate (38%) driftwood cover. Nest failure rates were high (32%– 95%), and arctic foxes (Alopex lagopus), alone or with polar bears (Ursus maritimus), appeared to be more destructive than glaucous gulls (Larus hyperboreus) to eider nests. Logistic regression was used to model common eider nest activity associated with driftwood cover and predators. When glaucous gulls were the only predators, more driftwood cover consistently increased the probability of nest activity. But when foxes were present, nest activity consistently decreased with increasing cover. Our models support our observations that nest cover was beneficial to eiders when glaucous gulls alone were predators. Driftwood cover may be most important for the thermal and structural protection it offers, rather than for the camouflage it provides. The energetic benefit provided by driftwood windbreaks coupled with the common eider’s behavioral response of decreased nest attendance, or increased exposure to avian depredation of nests as energy reserves are depleted during incubation, provides an explanatory mechanism for our model results. L’eider à duvet femelle (Somateria mollissima v-nigrum) choisit en général son site de nidification dans des zones ayant un couvert de bois flotté. Des études précédentes sur les eiders à duvet ont révélé qu’il existe une relation positive entre le succès de la couvée et le couvert ...